The Efficacy and Safety of Folate Receptor α‐Targeted Antibody‐Drug Conjugate Therapy in Patients With High‐Grade Epithelial Ovarian, Primary Peritoneal, or Fallopian Tube Cancers: A Systematic Review and Meta‐Analysis - Eun Taeg Kim; Ji Hyun Kim; Eun Young Park; In Hye Song; Han Song Park; Sang‐Yoon Park; Myong Cheol Lim (Cancer Medicine)
ABSTRACT Background Antibody‐drug conjugates (ADC) have emerged as a highly promising systemic option in the treatment of recurrent ovarian cancer. The present study aimed to evaluate the treatment efficacy of folate receptor α (FRα)‐targeting ADCs, associated treatment‐related adverse events (TRAEs), and their impact on treatment safety. Methods We conducted an electronic search to identify prospective trials of single‐agent ADCs targeting FRα and those combined with chemotherapy in recurrent ovarian cancer. Information regarding the objective response rate (ORR) and TRAEs was collectively analyzed, and differences in subgroups based on FRα receptor expression levels were investigated. The protocol was registered with PROSPERO (CRD42023491151). Results Ten studies with a total of 940 patients (859 treated with Mirvetuximab soravtansine‐gynx (MIRV)), 45 with Farletuzumab Ecteribulin (MORAb‐202), and 36 with Luveltamab Tazevibulin (STRO‐002) were included in this meta‐analysis. Based on the pooled data, the ORR of the entire cohort was 37% (95% CI: 0.30–0.43), while that of the high‐FRα expression group was 34% (95% CI: 0.26–0.42). The incidence of grade ≥ 3 adverse events was 27% (95% CI: 0.19–0.36). Conclusion FRα‐targeting ADCs, including MIRV, demonstrated definite efficacy and good safety as novel choices for second‐line and beyond treatment of advanced or recurrent ovarian cancer. Patients with high FRα expression showed ORR and PFS benefits similar to those in the overall cohort.